Cover Feature: Probing Individual Cuprous Oxide Microcrystals towards Carbon Dioxide Reduction by using In Situ Raman‐coupled Scanning Electrochemical Microscopy (ChemElectroChem 3/2022). Issue 3 (28th December 2021) - Steimecke, Matthias; Araújo‐Cordero, Ana María; Dieterich, Emil; Bron, Michael
Abstract : The Cover Feature illustrates the simultaneous probing of a cuprous oxide microcrystal by Raman and Scanning Electrochemical Microscopy (SECM) during CO2 electro‐reduction. Structural changes as well as products formed by carbon dioxide reduction can be determined. More information can be found in the Article by M. Steimecke et al .